2020
DOI: 10.4102/sajesbm.v12i1.261
|View full text |Cite
|
Sign up to set email alerts
|

Exploring migrant micro-entrepreneurs’ use of social capital to create opportunity in South Africa’s informal market: A qualitative approach

Abstract: hold significant job creation potential'. Viswanathan et al. (2012), and later Viswanathan et al. (2014), suggested that this is because of the intense personal relationships that develop because of the multiple and continuous interactions, which create the need to commit socially to the Background: Migrants operating micro-enterprises in rural communities of South Africa is a common phenomenon. These entrepreneurs live in communities they serve, and their enterprises are embedded in the 'social fabric' of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The literature records some strategies used to overcome challenges faced. Some call on African immigrants to take a social responsibility to allow their integration into society (Van der Walt and Whittaker, 2020). Conversely, the responsibility should also rest with the locals to support the integration of Jones and Muller (2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature records some strategies used to overcome challenges faced. Some call on African immigrants to take a social responsibility to allow their integration into society (Van der Walt and Whittaker, 2020). Conversely, the responsibility should also rest with the locals to support the integration of Jones and Muller (2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, young and formally educated manufacturers from both sites also reported that they used mobile applications such as WhatsApp to contact their friends in securing raw materials to ensure the continuity of their business operations. Recent studies also note that entrepreneurs in SMEs use their life experience and social connections to access resources to create opportunity (Van der Walt and Whittaker, 2020; Mennens et al , 2018). However, the prices of acquiring from the local scrapyards were significantly higher due to the increased demand of locally made materials, as the formal companies were closed down:…”
Section: Results and Interpretationmentioning
confidence: 99%
“…We also noted that recruitment and sub-contracting of jobs in the sector was tied to family and friendship connections. The economic and social value entrenched in these symbiotic relationships provided opportunities and potential for job creation (Van der Walt and Whittaker, 2020). A recent study also points out that informal methods of knowledge acquisition, such as the apprenticeship system and indigenous knowledge systems are key in informal settings (Jegede, 2020).…”
Section: Results and Interpretationmentioning
confidence: 99%
“…Under this arrangement, young women who are brought into the informal workspaces face the challenge of being segregated into particular roles that are deemed fit for women as patriarchal notions from society are imported into the workplace. Previous studies also noted that recruitment of jobs in the informal economy was tied to family and friendship connections (van der Walt & Whittaker, 2020). The informal training system of training often neglects training on skills for the management of funds, existing mostly for survivalist livelihoods.…”
Section: Methodsmentioning
confidence: 97%